MPL Adjuvant Contains Competitive Antagonists of Human TLR4 - Wang, Yi-Qi; Bazin-Lee, Hélène; Evans, Jay T.; Casella, Carolyn R.; Mitchell, Thomas C. (Frontiers in Immunology, 2020)
Monophosphoryl lipid A (MPL) is the first non-alum vaccine adjuvant to achieve widespread clinical and market acceptance, a remarkable achievement given that it is manufactured from a Salmonella enterica endotoxin. To understand how MPL successfully balanced the dual mandate of vaccine design – low reactogenicity with high efficacy – clinical and research grade MPL were evaluated in human and mouse cell systems. Stimulatory dose response curves revealed that most preparations of MPL are much more active in mouse than in human cell systems and that the limited efficacy observed in human cells correlated with TLR4 inhibitory activity that resulted in a partial agonist profile. Further analysis of the major components of MPL adjuvant prepared synthetically identified two structural variants that functioned as competitive antagonists of human TLR4. A partial agonist profile could be recapitulated and manipulated by spiking synthetic agonists with synthetic antagonists to achieve a broad dose range over which TLR4 stimulation could be constrained below a desired threshold. This report thus identifies mixed agonist-antagonist activity as an additional mechanism by which MPL adjuvant is detoxified, relative to its parental LPS, to render it safe for use in prophylactic vaccines.